2019
DOI: 10.1007/s40519-019-00644-5
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of the reliability and validity of the Italian version of the schema mode inventory for eating disorders: short form for adults with dysfunctional eating behaviors

Abstract: Purpose To examine the psychometric properties and the factorial structure of the Italian version of the schema mode inventory for eating disorders-short form (SMI-ED-SF) for adults with dysfunctional eating patterns. Methods 649 participants (72.1% females) completed the 64-item Italian version of the SMI-ED-SF and the eating disorder examination questionnaire (EDE-Q) for measuring eating disorder symptoms. Psychometric testing included confirmatory factor analysis (CFA) and internal consistency. Multivariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Due to a non-perfect normal distribution, Robust Maximum Likelihood estimator (MLR) was used to confirm the factorial structure of the Italian WSSQ. The MLR is a 'robust' variant of Maximum likelihood-which has many advantages over other estimators; i.e., computational efficiency [58]-providing robust standard errors and mean-adjusted χ 2 statistics that are robust to non-normality and the violation of independence-of-observation assumption [45,46,[58][59][60][61]. Model fit was tested using the χ 2 statistic and the goodnessof-fit indices [45,46,62]: (A) the Root-Mean Square Error of Approximation (RMSEA) [63], (B) the Comparative Fit Index (CFI) [64] and (C) the Standard Root Mean square Residual (SRMR) [65].…”
Section: Discussionmentioning
confidence: 99%
“…Due to a non-perfect normal distribution, Robust Maximum Likelihood estimator (MLR) was used to confirm the factorial structure of the Italian WSSQ. The MLR is a 'robust' variant of Maximum likelihood-which has many advantages over other estimators; i.e., computational efficiency [58]-providing robust standard errors and mean-adjusted χ 2 statistics that are robust to non-normality and the violation of independence-of-observation assumption [45,46,[58][59][60][61]. Model fit was tested using the χ 2 statistic and the goodnessof-fit indices [45,46,62]: (A) the Root-Mean Square Error of Approximation (RMSEA) [63], (B) the Comparative Fit Index (CFI) [64] and (C) the Standard Root Mean square Residual (SRMR) [65].…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies [80], the pool of items of the structured interview was developed using a two-step procedure [46,[81][82][83][84].…”
Section: Measures: (Development Of) the Structured Interviewmentioning
confidence: 99%
“…(Mannarini et al, 2013;Ratti et al, 2017;Parola, 2020;Rossi Ferrario and Panzeri, 2020) or a chronic (stressing) condition (e.g., aging difficulties, caregiving, obesity, dyadic conflicts) (Pietrabissa et al, 2017;Faccio et al, 2019;Panzeri et al, 2019;Balestroni et al, 2020;Panzeri and Rossi Ferrario, 2020;Parola and Felaco, 2020) may consistently help individuals to decrease denial and accept their situation, thus reducing the associated psychological distress (Elliott, 2011;Stuntzner and Dalton, 2015;Rossi Ferrario et al, 2019). Scientific literature showed that low levels of forgiveness may play a crucial role in patients with obesity who may show maladaptive behaviors, such as emotional eating and food addiction (Manzoni et al, 2020), as well as several related psychological issues (Mannarini and Boffo, 2014;Balottin et al, 2017;Manzoni et al, 2018;Simpson et al, 2018;Rossi and Mannarini, 2019;Pietrabissa et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%